China's string of pearls in Indian ocean and its security implication for India - Ain, Qurat Ul. (South Asian Journal of Socio-Political Studies)
China isemerging the great power of 21th centruy ports and pipeline become veins and capillaries for the survival of great nations. - Reproduced
Keywords: String of pearls, China, Indian ocean, strategic, Middle east, Security, Economic